Functionalization of graphene - a critical overview of its improved physical, chemical and electrochemical properties - Singh, Ramesh Kumar; Nalajala, Naresh; Kar, Tathagata; Schechter, Alex (Surface Engineering of Graphene, 2019)
Graphene, the 2D allotrope of carbon, is reported to be functionalized with a plethora of organic and inorganic species. This functionalization imparts significant improvement in the physical, chemical and electrochemical properties of graphene. The covalent and non-covalent functionalization of graphene with electron-rich organic moieties and heteroatoms is focused on different sections of this chapter. The focus is laid on the improvement in physical, chemical and electrochemical properties of graphene achieved through this functionalization. The enhancement in electrocatalytic activity of non-metal-doped graphene towards the oxygen reduction reaction, methanol oxidation reaction and photocatalysis is covered. Towards the end, the potential uses of functionalized graphene for selected applications like biosensors, fuel cells and dye-sensitized solar cells are also discussed.